Gastric Dilatation and Volvulus in a Red Panda (Ailurus fulgens). Issue 8 (27th January 2014) - Neilsen, Colleen; Mans, Christoph; Colopy, Sara A.
Abstract Objective To describe the successful management of gastric dilatation and volvulus (GDV) in a red panda. Study Design Clinical report. Animals Red panda diagnosed with GDV. Results A 12‐year‐old male red panda (Ailurus fulgens) was evaluated for acute onset inappetence, staggering, collapse, and tachypnea. Gastric dilatation and volvulus (GDV) was diagnosed by radiography, abdominal ultrasonography, and exploratory celiotomy. Torsion of the stomach was corrected and an incisional gastropexy performed to prevent recurrence. No organs were devitalized, no other abnormalities detected, and the red panda recovered fully within 72 hours. Conclusions GDV should be considered as a differential diagnosis for red pandas presenting with acute onset of unspecific signs such as collapse, inappetence, and abdominal distension. GDV in red pandas can be diagnosed and successfully treated as described in dogs.